Visceral adiposity index and lipid accumulation product as diagnostic markers of metabolic syndrome in South Indians with polycystic ovary syndrome - Zeinab Naghshband; Lakshmi Kumar; Sonia Mandappa; Ashitha S Niranjana Murthy; Suttur S Malini (Wolters Kluwer Medknow Publications, 2021)
Background: Cardiovascular disease (CVD) is one of the debilitating consequences of polycystic ovary syndrome (PCOS). Early diagnosis of metabolic syndrome (MetS) with a simple but accurate method can reduce the risk of progression to CVD in PCOS. Aims: This study aimed to determine the accuracy of various anthropometric indices and lipid accumulation product (LAP), in assessing the risk of MetS in PCOS. Settings and Design: This is a cross-sectional study including 150 PCOS women and 100 control subjects. Materials and Methods: Anthropometric parameters were measured and calculated. Lipid profile, fasting plasma glucose (FPG), and insulin were estimated. MetS was detected according to the International Diabetes Federation criteria. Statistical Analysis: Logistic regression and receiver operating characteristic curve analysis were applied to determine the potential association of anthropometric indices such as body mass index, waist circumference (WC), waist-to-hip ratio, waist-to-height ratio, conicity index (CI), visceral adiposity index (VAI), abdominal volume index (AVI), body adiposity index (BAI), and a body shape index (ABSI) and LAP with MetS. Results: In our study of PCOS women of the south Indian population, the prevalence of MetS was 59.3%, which was higher than other populations and the cutoff values of VAI and LAP were 6.05 and 53, respectively. VAI showed the strongest association with MetS, followed by diastolic blood pressure BP, FPG, and LAP. Conclusions: We recommend VAI and LAP as new indices for MetS diagnosis. As these indices exhibit population specificity, it is imperative that independent cutoffs are determined for every demographic population.